2004
DOI: 10.1002/eji.200424887
|View full text |Cite
|
Sign up to set email alerts
|

Association of hepatitis C virus envelope proteins with exosomes

Abstract: As the human tetraspanin CD81 binds hepatitis C virus (HCV) envelope glycoprotein E2, we addressed the role CD81 may play in cellular trafficking of HCV envelope proteins. Studies on HCV life cycle are complicated by the lack of a robust cell culture system; we therefore transfected mammalian cells with HCV E1-E2 cDNA, with or without human CD81 (huCD81) cDNA. In the absence of huCD81, HCV envelope proteins are almost completely retained in the endoplasmic reticulum. Instead, when huCD81 is present, a fraction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
175
1
5

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 187 publications
(194 citation statements)
references
References 36 publications
9
175
1
5
Order By: Relevance
“…In addition, several reports suggest the presence of MHCcontaining exosome-like structures in rat [34] or human [35,36] blood. However, these reports have relied on dot blotting or Western blotting combined with ultracentrifugation to demonstrate the presence of MHC in exosomal pellets prepared from blood.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, several reports suggest the presence of MHCcontaining exosome-like structures in rat [34] or human [35,36] blood. However, these reports have relied on dot blotting or Western blotting combined with ultracentrifugation to demonstrate the presence of MHC in exosomal pellets prepared from blood.…”
Section: Discussionmentioning
confidence: 99%
“…34,35 Nevertheless, differences in phospholipid molecular species composition and higher neutral lipid content distinguish LVPs between specific TRLs defined by their density. Interestingly, most LVPs resemble empty, nucleocapsid-free subviral particles, similar to recombinant subviral envelope particles produced in vitro, whereas nucleocapsid-containing LVPs are only a subset of the whole LVP ensemble.…”
Section: Discussionmentioning
confidence: 99%
“…Enrichment of exosomes was performed according to Masciopinto et al [25]. In this former study, the CD81 enriched exosomal fraction was identified by immunoblotting in the pellets from the fourth (p4) and -mainlythe fifth (p5) centrifugation fraction from plasma [25].…”
Section: Isolation Of Cd81 From Serum and Plasmamentioning
confidence: 99%
“…Enrichment of exosomes was performed according to Masciopinto et al [25]. In this former study, the CD81 enriched exosomal fraction was identified by immunoblotting in the pellets from the fourth (p4) and -mainlythe fifth (p5) centrifugation fraction from plasma [25]. In the current study, differential centrifugation was performed at 200 g for 10 min (p1), at 500 g (p2), at 2000 g for 15 min (p3), at 10,000 g for 30 min (p4), and finally 100,000 g for 30 min (p5).…”
Section: Isolation Of Cd81 From Serum and Plasmamentioning
confidence: 99%
See 1 more Smart Citation